2018
DOI: 10.1007/s10545-017-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of tandem mass spectrometry to the diagnosis of lysosomal storage disorders

Abstract: Tandem mass spectrometry (MS/MS) is a highly sensitive and specific technique. Thanks to the development of triple quadrupole analyzers, it is becoming more widely used in laboratories working in the field of inborn errors of metabolism. We review here the state of the art of this technique applied to the diagnosis of lysosomal storage disorders (LSDs) and how MS/MS has changed the diagnostic rationale in recent years. This fine technology brings more sensitive, specific, and reliable methods than the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 205 publications
0
16
0
1
Order By: Relevance
“…We reported a sensitive multiplex method to measure various lysosphingolipids in the plasma for the diagnosis of Fabry, Gaucher, Krabbe, Niemann-Pick type A, B and C diseases and prosaposin deficiency [20,24]. Similar studies were performed by other groups [5,[21][22][23]. Despite the different analytical approaches in terms of sample preparation, internal standard and LC-MS/MS analysis, all these studies confirmed that a simultaneous LysoSL quantification could be a useful first-tier test to screen patients suspected for sphingolipidoses.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We reported a sensitive multiplex method to measure various lysosphingolipids in the plasma for the diagnosis of Fabry, Gaucher, Krabbe, Niemann-Pick type A, B and C diseases and prosaposin deficiency [20,24]. Similar studies were performed by other groups [5,[21][22][23]. Despite the different analytical approaches in terms of sample preparation, internal standard and LC-MS/MS analysis, all these studies confirmed that a simultaneous LysoSL quantification could be a useful first-tier test to screen patients suspected for sphingolipidoses.…”
Section: Discussionmentioning
confidence: 80%
“…LysoGM1 and LysoGM2 have been proposed to be biomarkers of other two ultra-rare lysosomal diseases, the GM1 and GM2 gangliosidoses. The sensitivity of these markers in the plasma has been reported to be poor and critical for later onset forms [5,21]. We analyzed these markers in a limited number of patients (GM1 n = 1; GM2 n = 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the unknown peak was reported to be useful for NPC diagnostic screening [95] and immediately cited in many guidelines [3,96,97]. Multiplex analyses of Lyso-SM-509 were useful for differentiation from other lysosomal diseases [98]. The differentiation between NPC and NP-A/B [99,100] and correlations between cholenoic acids and Lyso-SM-509 have also been reported [101].…”
Section: N-palmitoyl-o-phosphocholine-serine Previously Referred To mentioning
confidence: 98%
“…Measurements of plasma lysosphingomyelin levels also have been reported to be potentially useful in NPC disease (Welford et al, 2014). Lysosphingolipids, N-deacylated versions of their precursor sphingolipids, appear to be elevated in multiple disorders due to deficiencies of enzymes responsible for the breakdown of complex sphingolipids (Piraud et al, 2018). Moreover, lysosphingolipid measurements have attracted attention since compared to their acylated precursors, their accumulation is often up to an order of magnitude higher in these disease states, suggesting that they could be more reliable biomarkers than the other previously discussed sphingolipid metabolites (Welford et al, 2014).…”
Section: Sphingolipid Biomarkers Of Npcmentioning
confidence: 99%